LEMBAGA EKSAMINASI PERTANAHAN SEBAGAI ALTERNATIF MODEL PENYELESAIAN SENGKETA DI BIDANG PERTANAHAN - M. Hamidi Masykur (Departemen Hukum Perdata, 2016)
Land problem is an issue that often causes dispute prolonged in the dynamics of lives of many Indonesian’s people. Government efforts to serious in minimize or reduce conflict of agrarian affairs (land) proven with the establishment of decree of the Regulation of The National Land Agency Republic Indonesia Number 12 Year 2013 about Land Examination. Land Examination institutions have the authority to resolve the conflict through researchers land, examiner and give the recommendations of the decision and the concept of the decision to give regulation, conversion/affirmation/recognition, the cancellation of land rights published The National Land Agency. In 2011 the government also has imposed The National Land Agency decree of Regulation of The National Land Agency Republic Indonesia Number 12 Year 2013. The regulation is the institutional mechanism orders the title land cases in land dispute resolution. The question is then could land examination institutions (Regulation of The National Land Agency Republic Indonesia Number 12 Year 2013) as a land dispute resolution outside of court (alternative dispute resolution) able to answer the problem of land conflicts that become contributors to the case in the supreme court. An excess of this institution is examination can settle the dispute quickly, and his ruling is a win win solution, reduce the cost of conventional litigation and withdrawal of the usual time happened, prevent a legal dispute that usually go to court. The weakness of the institution examination this is a lack of socialization, not all the areas of The National Land Agency forming Examination Team. Optimization of land examination institutions required to land dispute settlement can be immediately solved without judicial mechanisms of course take a long time and not completed.